Autorrepresentação na escultura : Louise Bourgeois, Jorge Molder, Alberto Carneiro - Ferreira, Rui Freitas, 1991- (2017)
With the intention of deepening the meaning and what is meant by self-representation on sculpture, the dissertation focuses on the analysis of three sculptors who make their work into a self-representation, through an introductory approach to self-portrait, as the beginning of a self-representation. The self-representation starts from a personal experience, or life experience, in which the artist represents it on the “third person”, incorporating a theatrical dimension. The theatrical performance can be based on personal facts or a “mixture” of memories and personal episodes with philosophical or literary references. The self-representation comes as a deepening of consciousness, in which the sculptor search in the background of the being an exterior that “replace” or that “mimics” incompletely, that is, as simulacrum, making self-representation the junction of these two ideas, namely the theatrical dimension and simulacrum, an externality is linked to which artist